4-Aminopyridinium cis-2-carboxycyclohexane-1-carboxylate - Smith, Graham (International Union of Crystallography, 2011)
In the structure of the title molecular salt, C(5)H(7)N(2) (+)·C(8)H(11)O(4) (−), the cis monoanions associate through short O—H⋯O hydrogen bonds in the carboxylic acid groups [graph set C(7)], forming zigzag chains which extend along the c axis. These are interlinked through pyridinium and amine N—H⋯O hydrogen bonds, giving a three-dimensional network structure.